Nutritional Disparities among Women in Urban India (Journal of Health, Population and Nutrition, 2014)
The paper presents a wealth quartile analysis of the urban subset of the third round of Demographic Health Survey of India to unmask intra-urban nutrition disparities in women. Maternal thinness and moderate/ severe anaemia among women of the poorest urban quartile was 38.5% and 20% respectively and 1.5-1.8 times higher than the rest of urban population. Receipt of pre- and postnatal nutrition and health education and compliance to iron folic acid tablets during pregnancy was low across all quartiles. One-fourth (24.5%) of households in the lowest urban quartile consumed salt with no iodine content, which was 2.8 times higher than rest of the urban population (8.7%). The study highlights the need to use poor-specific urban data for planning and suggests (i) routine field assessment of maternal nutritional status in outreach programmes, (ii) improving access to food subsidies, subsidized adequately-iodized salt and food supplementation programmes, (iii) identifying alternative iron supplementation methods, and (iv) institutionalizing counselling days. DOI: http://dx.doi.org/10.3329/jhpn.v31i4.20052 J HEALTH POPUL NUTR 2013 Dec; 31(4): 531-537